Sistem Informasi Geografis Petshop Di Kota Padang Berbasis Website - Febrian, Wahyu; Sularno, Sularno; Mulya, Dio Prima (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
The amount of tertiary requirements that individuals consume is rising along with the times. People have different priorities, and things like hobbies, wealth, and social standing can affect this priority scale. Keeping animals as pets, including cats, dogs, birds, snakes, and others, is one example of this pastime. The growing popularity of pets creates a significant demand for a location that can adequately house and offer a range of equipment, supplies, and services connected to pet upkeep and care. Pets Keep is a site that offers products to satisfy pet needs and animal care services, and there are additional pet lodgings such places where you may leave your pet, veterinary clinics, and grooming or puppy salons for caring for animals. A pet store is a location that offers supplies for pets and animal care services, and there are also pet hotels—places where people may leave their pets—as well as difficult-to-find pet clinics for veterinarian checkups, pet grooming, and pet salons for animal care find in PadangCity Aera.